Molecular features and transmission of NDM-producing Enterobacterales in Israeli hospitals. (14th January 2023) - Adler, Amos; Ghosh, Hiren; Gross, Andrea; Rechavi, Amit; Lasnoy, Michal; Assous, Marc V; Geffen, Yuval; Darawshe, Basel; Wiener-Well, Yonit; Grundmann, Hajo; Reuter, Sandra
Abstract: Objectives: NDM-producing Enterobacterales (NDME) account for 34.9% of new carbapenemase-producing Enterobacterales cases in Israeli hospitals. The goals of this study were to characterize the genomic composition of NDME isolates and mobile genetic elements (MGEs) and to identify NDME transmission events (TEs). Methods: The study was conducted at the Tel-Aviv Sourasky, Rambam and Sha'are-Zedek Medical Centers (TASMC, RMC and SZMC, respectively). All NDME isolates detected between January 2018 and July 2019 were included. Phylogenetic analysis was based on core-genome SNP distances. Core-genome distance of ≤5 SNPs between isolates from patients with overlapping hospitalization periods was suggestive of a potential TE. MGEs were classified by comparison of the bla NDM gene flanking regions. Results: The study included 212 NDME isolates from 203 patients, including 104 isolates from TASMC, 30 isolates from RMC and 78 isolates from SZMC. The majority of isolates ( n = 157; 74%) harboured the bla NDM-1 gene, followed by the bla NDM-5 ( n = 48) and bla NDM-15 genes ( n = 7). The most common NDME species were Klebsiella pneumoniae ( n = 67), Escherichia coli ( n = 65) and Enterobacter cloacae ( n = 45), all showing a highly diverse clonal structure. Most bla NDM-1 -harbouring isolates (134/157; 85%) were divided into nine different MGE modules, variably distributed across species and hospitals. The numbers of post-admission acquisition cases ( n = 118) that could be linked to other cases by both molecular and epidemiological criteria were 13/58 (24.2%), 3/48 (6.3%) and 4/12 (33.3%) in TASMC, SZMC and RMC, respectively. Conclusions: The study depicted a complex and diverse population structure, suggesting that NDME had not spread via clonal expansion.